Analysis of appraisals related to personalized education corresponding to the pedagogical approach of Victor Garcia Hoz - Vera Tapia, Marcela (2020)
It is presented appreciations and analysis on personalized education taking into account the responses of educators with extensive experience in this pedagogical proposal. The scenarios or questions correspond to nine aspects: The challenge of the complexity of learning teaching, opinion on this approach, innovation, tradition, teacher attitude, dimension of person, teacher, student, and parent. The answers are contrasted according to the approach of a pedagogy of the person proposed by Víctor García Hoz. The objectives were to see the dynamics of the interdependence of some aspects of personalized education based on nine criteria of analysis. Ten participants were interviewed using a questionnaire with nine questions and the answers were recorded on  video and then transcribed the text to enable the respective analysis. The results are presented using figures that illustrate in a summary and representative manner, as far as possible, the considerations derived from the responses. The analysis emphasizes the complexity of the topic and suggests some questions to continue research on this topic.